2021
DOI: 10.1210/clinem/dgab810
|View full text |Cite
|
Sign up to set email alerts
|

Physical Fitness and Cardiovascular Risk Factors in Novel Diabetes Subgroups

Abstract: Context Physical inactivity promotes insulin resistance and increases the risk of diabetes and cardiovascular disease. Recently introduced clustering based on simple clinical measures identified diabetes subgroups (clusters) with different risks of diabetes-related comorbidities and complications. Objective This study aims to determine differences in physical fitness and cardiovascular risk between diabetes subgroups and a gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 56 publications
2
10
0
1
Order By: Relevance
“…While recent meta-analyses showed impaired endothelial function in T1D ( 26 ) and T2D compared with healthy people ( 27 ), another recent population-based study suggested no association between diabetes and endothelial function ( 11 ). Previous studies reported reduced FMD only for overt T2D, but not for participants with impaired glucose tolerance ( 28 ) or at the time of diabetes onset ( 19 ). The present study adds to these data that endothelial dysfunction may not be necessarily present at diagnosis, but rapidly develop despite only minor changes in fat mass and glycemic control, and no changes in lipid profile in metabolically well-controlled patients with T2D during 5 years.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…While recent meta-analyses showed impaired endothelial function in T1D ( 26 ) and T2D compared with healthy people ( 27 ), another recent population-based study suggested no association between diabetes and endothelial function ( 11 ). Previous studies reported reduced FMD only for overt T2D, but not for participants with impaired glucose tolerance ( 28 ) or at the time of diabetes onset ( 19 ). The present study adds to these data that endothelial dysfunction may not be necessarily present at diagnosis, but rapidly develop despite only minor changes in fat mass and glycemic control, and no changes in lipid profile in metabolically well-controlled patients with T2D during 5 years.…”
Section: Discussionmentioning
confidence: 94%
“…Images of the brachial artery were obtained before and 3 minutes after administration. FMD and NMD were calculated as the quotient between the arterial baseline diameter and the diameter after cuff deflation and after medication administration, respectively, using Brachial-Analyzer software (Medical Imaging Applications, Coralville, Iowa, USA) ( 19 ). All data underwent intensive quality control check.…”
Section: Methodsmentioning
confidence: 99%
“…The independent effects of physical activity are relevant to our findings and extend to others that have investigated differences across T2DM subtypes. For instance, previous research conducted in 746 participants with recent‐onset T2DM (<12 months), demonstrated that those in the OB cluster display a low cardiorespiratory fitness level, relative to both control (non‐T2DM) and other T2DM clusters 39 . As such individuals are prime candidates for targeted lifestyle interventions, it is important not to focus on the potential for weight loss as the sole outcome from increasing physical activity/fitness levels, but rather to suggest that it influences the composition and maintenance of weight loss alongside other key health metrics (e.g., HbA1c).…”
Section: Discussionmentioning
confidence: 99%
“…38 The independent effects of physical activity are relevant to clusters. 39 As such individuals are prime candidates for targeted lifestyle interventions, it is important not to focus on the potential for weight loss as the sole outcome from increasing physical activity/ fitness levels, but rather to suggest that it influences the composition and maintenance of weight loss alongside other key health metrics (e.g., HbA1c).…”
Section: Discussionmentioning
confidence: 99%
“…T2DM is associated with an elevated risk for CVD and poor recovery after MI. Notably, severe insulin resistance found in a subset of patients with diabetes is highly associated with cardiovascular complications [27], however, the molecular mechanisms linking insulin action and heart disease are not well understood. In the present study, we demonstrate that lack of the insulin signaling protein TBC1D4 in mice abrogates cardiac glucose uptake in response to insulin and aggravates cardiac damage after myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%